Psychometric study of the behavior questionnaire antisocial - criminal in students high school - UGEL No. 2 Lima - Díaz Gamarra, Patricia del Pilar (2019)
The objective of this research was to adapt the Antisocial-Delictive Conduct (A-D) questionnaire designed by Seisdedos. The sample consisted of 400 high school students from the UGEL N ° 2 in Lima, aged between 12 and 18 years. The results showed that the Antisocial-Delictive Conduct questionnaire has high reliability due to internal consistency, under Cronbach’s alpha coefficient = 0.963; and the two halves method, where the Spearman Brown statistic yielded an index of 0.882. On the other hand, the instrument demonstrates content validity since agreement was found among judges, as well as the construct validity of the test was determined, through the item test analysis, finding significant elements and dimensions (p= .00), in addition, the factorial analysis made to the questionnaire confirms the existence of two dimensions (antisocial and delinquency) that explain 52.25% of the variance. Finally, the scales for the investigated sample were constructed.